High risk stigmata and treatment strategy for acute lower gastrointestinal bleeding: a nationwide study in Japan - Aoki, Tomonori; Sadashima, Eiji; Kobayashi, Katsumasa; Yamauchi, Atsushi; Yamada, Atsuo; Omori, Jun; Ikeya, Takashi; Aoyama, Taiki; Tominaga, Naoyuki; Sato, Yoshinori; Kishino, Takaaki; Ishii, Naoki; Sawada, Tsunaki; Murata, Masaki; Takao, Akinari; Mizukami, Kazuhiro; Kinjo, Ken; Fujimori, Shunji; Uotani, Takahiro; Fujita, Minoru; Sato, Hiroki; Hayakawa, Yoku; Fujishiro, Mitsuhiro; Kaise, Mitsuru; Nagata, Naoyoshi; CODE BLUE-J Study collaborators; Suzuki, Sho; Narasaka, Toshiaki; Hayasaka, Junnosuke; Funabiki, Tomohiro; Kinjo, Yuzuru; Mizuki, Akira; Kiyotoki, Shu; Mikami, Tatsuya; Gushima, Ryosuke; Fujii, Hiroyuki; Fuyuno, Yuta; Hikichi, Takuto; Toya, Yosuke; Narimatsu, Kazuyuki; Manabe, Noriaki; Nagaike, Koji; Kinjo, Tetsu; Sumida, Yorinobu; Funakoshi, Sadahiro; Kobayashi, Kiyonori; Matsuhashi, Tamotsu; Komaki, Yuga; Watanabe, Kazuhiro; Niikura, Ryota; Suzuki, Nobumi; Tsuji, Yosuke (Endoscopy, 2024)
Background The rebleeding risks and outcomes of endoscopic treatment for acute lower gastrointestinal bleeding (ALGIB) may differ depending on the bleeding location, type, and etiology of stigmata of recent hemorrhage (SRH) but have yet to be fully investigated. We aimed to identify high risk endoscopic SRH and to propose an optimal endoscopic treatment strategy.Methods We retrospectively analyzed 2699 ALGIB patients with SRH at 49 hospitals (CODE BLUE-J Study), of whom 88.6 % received endoscopic treatment.Results 30-day rebleeding rates of untreated SRH significantly differed among locations (left colon 15.5 % vs. right colon 28.6 %) and etiologies (diverticular bleeding 27.5 % vs. others [e. g. ulcerative lesions or angioectasia] 8.9 %), but not among bleeding types. Endoscopic treatment reduced the overall rebleeding rate (adjusted odds ratio [AOR] 0.69; 95 %CI 0.49–0.98), and the treatment effect was significant in right-colon SRH (AOR 0.46; 95 %CI 0.29–0.72) but not in left-colon SRH. The effect was observed in both active and nonactive types, but was not statistically significant. Moreover, the effect was significant for diverticular bleeding (AOR 0.60; 95 %CI 0.41–0.88) but not for other diseases. When focusing on treatment type, the effectiveness was not significantly different between clipping and other modalities for most SRH, whereas ligation was significantly more effective than clipping in right-colon diverticular bleeding. Conclusions A population-level endoscopy dataset allowed us to identify high risk endoscopic SRH and propose a simple endoscopic treatment strategy for ALGIB. Unlike upper gastrointestinal bleeding, the rebleeding risks for ALGIB depend on colonic location, bleeding etiology, and treatment modality.